Pyrvinium Pamoate Synergizes with Azoles in vitro and in vivo to Exert Antifungal Efficacy Against Candida auris and Other Candida Species - Zhang J; Li G; Hu J; Tan J; Zhang H; Zhou Y (Infection and Drug Resistance)
Jinqing Zhang,1,* Gaolian Li,2,* Jing Hu,3,* Jingwen Tan,4 Heng Zhang,5 Yizheng Zhou5 1Department of Dermatology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Gynaecology, Jingzhou Hospital Affiliated to Yangtze University, Jingzhou, Hubei Province, People’s Republic of China; 3Department of Clinical Medicine, Xiangyang Polytechnic, Xiangyang, Hubei Province, People’s Republic of China; 4Department of Medical Mycology, Shanghai Skin Disease Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 5Department of Clinical Laboratory, Jingzhou Hospital Affiliated to Yangtze University, Jingzhou, Hubei Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yizheng Zhou, Email zhou_yizheng@163.comIntroduction: Treating infections caused by azole-resistant Candida spp. poses a significant challenge. Previous research has indicated that pyrvinium pamoate (PP) has the potential to augment the antifungal efficacy of azole antifungals against filamentous fungi. The objective of this study was to investigate the antifungal properties of PP, both independently and in conjunction with azoles, against Candida auris and other Candida spp.Materials and Methods: A total of 21 clinical Candida spp. strains and five azoles were assessed. The antifungal efficacy of PP, either alone or in combination with azoles, was tested according to the reference method. Galleria mellonella larvae were employed to evaluate the antifungal efficacy of PP and/or azoles in the treatment of C. auris infections in vivo.Results: When used to treat these different fungal isolates in vitro, the single-agent efficacy of PP was relatively poor, with minimum inhibitory concentration values ranging from 2 μg/mL - > 32 μg/mL. However, PP and azoles exhibited synergistic activity against the majority of analyzed C. albicans and C. auris isolates. To extend these results in vivo, G. mellonella was infected with C. auris strain AR385 and both survival and fungal burden were assessed for treated larvae. The inclusion of PP in combination with itraconazole, voriconazole, or posaconazole resulted in varying degrees of improvement in the survival rates of these larvae.Conclusion: Combining PP with azoles represents a promising approach to effectively disrupting the growth of azole-resistant C. auris and other Candida spp. such that it may be a promising anti-Candida therapeutic option.Keywords: Candida auris, pyrvinium pamoate, synergy azoles, Galleria mellonella